Disease‐induced decline of an apex predator drives invasive dominated states and threatens biodiversity. Issue 2 (7th March 2016) - Hollings, Tracey; Jones, Menna; Mooney, Nick; McCallum, Hamish
Abstract: Apex predators are important in protecting biodiversity through top‐down influence on food webs. Their loss is linked with competitive release of invasive mesopredators and species extinctions. The Tasmanian devil ( Sarcophilus harrisii ) has experienced severe declines over a 15‐yr period as a novel transmissible cancer has spread across its current geographic range. We surveyed the mammalian community, using hair traps, across the spatial extent of the devil's progressive population decline. We found increased activity of alien invasive species (feral cats, black rats), and reduced small and medium‐sized native prey species in response to the timing of the decline. In areas of long‐term devil decline, invasive species comprised a significantly larger proportion of the community. The results provide evidence that the devil plays a keystone role in Tasmania's ecosystem with their decline linked to a shift toward an invasive state and biodiversity loss in one of Australia's most intact faunal communities.